Activation of HRI is mediated by Hsp90 during stress through modulation of the HRI-Hsp90 complex - Berwal, Sunil K.; Bhatia, Varsha; Bendre, Arneya; Suresh, C. G.; Chatterjee, Sangeeta; Pal, Jayanta K. (International Journal of Biological Macromolecules, 2018)
Heme Regulated Inhibitor (HRI) is known to get activated in various stresses such as heme deficiency, heat shock, heavy metal toxicity etc. Heat shock protein 90 (Hsp90), a ubiquitous cytoplasmic protein interacts with HRI in order to regulate protein synthesis. However, it still remains to establish this interaction of HRI and Hsp90 at cellular levels and how this modulation of HRI activity is mediated by Hsp90 during stress. In the present report, using co-immunoprecipitation analysis we show that HRI interacts with Hsp90 and this association is independent of other co-chaperones in in vitro conditions. Further, analysis using truncated domains of HRI revealed that the K1 subdomain is essential for HRI - Hsp90 complex formation. Our in silico protein - protein interaction studies also indicated interaction of Hsp90 with K1 subdomain of HRI. Mammalian two hybrid assay validated this HRI - Hsp90 interaction at cellular levels. When the in vitro kinase assay was carried out with the co-immunoprecipitated complex of HRI - Hsp90, an increase in the kinase activity was observed resulting elevated levels of eIF2 alpha phosphorylation upon heavy metal stress and heat shock. Thus, our results clearly indicate modulation of HRI kinase activity with simultaneous Hsp90 association under stress conditions. (C) 2018 Elsevier B.V. All rights reserved.